(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
In the contemporary, increasingly globalized world, critical information literacy can be seen as essential for maintaining cultural diversity and for resistance and emancipation against oppression and cultural homogenization imposed by dominant forces. Thus, it seeks to reflect on possible contributions of critical information literacy against forms of oppression in the context of original peoples. Procedurally, it presents a set of analyzes and discussions resulting from bibliographical surveys carried out during the elaboration of the theoretical framework of a doctoral research, which has as its central theme critical information literacy in the context of indigenous peoples. It is considered that reflections on coloniality, especially the coloniality of knowledge, are essential for understanding the potential of critical information literacy as a strategy of resistance and overcoming conditions of subalternization, oppression, marginalization and exclusion because pass on the sociability of original peoples.